Phosphorylation pattern of Rubisco activase in Arabidopsis leaves. (30th September 2013) - Boex‐Fontvieille, E.; Daventure, M.; Jossier, M.; Hodges, M.; Zivy, M.; Tcherkez, G.; Adams, W.
Abstract Rubisco activase (RCA) is an ancillary photosynthetic protein essential for Rubisco activity. Some data suggest that post‐translational modifications (such as reduction of disulphide bridges) are involved in the regulation of RCA activity. However, despite the key role of protein phosphorylation in general metabolic regulation, RCA phosphorylation has not been well characterised. We took advantage of phosphoproteomics and gas exchange analyses with instant sampling adapted to Arabidopsis rosettes to examine the occurrence and variations of phosphopeptides associated with RCA in different photosynthetic contexts (CO2 mole fraction, light and dark). We detected two phosphopeptides from RCA corresponding to residues Thr 78 and Ser 172, and show that the former is considerably more phosphorylated in the dark than in the light, while the latter show no light/dark pattern. The CO2 mole fraction did not influence phosphorylation of either residue. Phosphorylation thus appears to be a potential mechanism associated with RCA dark inactivation, when Rubisco‐catalysed carboxylation is arrested. Since Thr 78 and Ser 172 are located in the N and Walker domains of the protein, respectively, the involvement of phosphorylation in protein–protein interaction and catalysis is likely.